MANAJEMEN PENGELOLAAN KELAS BERBASIS NILAI ISLAM DI PESANTREN DEA MALELA NTB - Nursyinsah, Rahma; Subagyo, Ahmad; Suhardi; Arsil, Fadhli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The modernization of Islamic education and changes in students’ learning behavior require pesantren to develop Islamic values-based classroom management that is effective, humanistic, and oriented toward religious character building. This study aims to analyze the management of Islamic values-based classroom management at Pesantren Dea Malela NTB and its implications for the effectiveness of students’ learning. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using open coding, axial coding, and selective coding techniques. The findings reveal that classroom management is implemented integratively through planning, implementation, supervision, and evaluation functions grounded in the values of adab, trustworthiness (amanah), discipline, ukhuwah, ihsan, and al-musāwah. These values are operationalized through religious habituation, teacher role modeling, dialogic communication, and integrated boarding school-based supervision. The study also finds that the humanistic-educative approach enhances student participation, creates a conducive learning environment, and strengthens Islamic character formation. This research contributes to the development of a conceptual model of Islamic classroom management within the context of modern pesantren education.